Mucin secretory action of capsaicin prevents high fat diet-induced gut barrier dysfunction in C57BL/6 mice colon - Vijay Kumar (Elsevier, 2022)
The gut barrier – including tight junction proteins (TJPs) and mucus layers, is the first line of defense against physical, chemical or pathogenic incursions. This barrier is compromised in various health disorders. Capsaicin, a dietary agonist of Transient receptor potential vanilloid 1 (TRPV1) channel, is reported to alleviate the complications of obesity. While it is well known to improve energy expenditure and metabolism, and prevent dysbiosis, the more local effects on the host gut – particularly the gut barrier and mucus system remain elusive. To investigate the effect of capsaicin on the gut barrier and mucus production and to understand the involvement of mucus, bacteria, and TRPV1 in these phenomena, we employed a diet-induced obesity model in C57BL/6 mice, and capsaicin (2 mg/kg/day p.o.) or mucin (1 g/kg/day p.o.) as interventions, for 12 weeks. Parameters like weight gain, glucose homeostasis, TJPs expression, mucus staining, intestinal permeability etc were studied. 16 S rDNA sequencing and in vitro Ca2+ measurement experiments were performed to explore the role of microbiota in the beneficial effects. Mucin feeding reflected several anti-obesity effects produced by capsaicin, suggesting that mucus modulation might play a crucial role in capsaicin-induced anti-obesity effects. 16 S rDNA sequencing and in vitro Ca2+ measurement experiments pointed to TRPV1 modulation by bacteria besides capsaicin. Capsaicin, bacteria and the host mucus system seem to act in a cyclic cascade involving TRPV1, which can be activated by capsaicin and various bacteria. These findings provide new insight into the role of TRPV1 in maintaining a healthy gut environment.